Prognostic significance of metabolic tumor volume in patients with piriform sinus carcinoma treated by radiotherapy with or without concurrent chemotherapy. Issue 11 (3rd May 2016) - Yabuki, Kenichiro; Sano, Daisuke; Shiono, Osamu; Arai, Yasuhiro; Takahashi, Hideaki; Chiba, Yoshihiro; Tanabe, Teruhiko; Nishimura, Goshi; Takahashi, Masahiro; Taguchi, Takahide; Kaneta, Tomohiro; Hata, Masaharu; et al.
Abstract: Background: The purpose of this study was to elucidate the prognostic significance of the pretreatment metabolic tumor volume (MTV) in patients with piriform sinus carcinoma treated by radiation‐based therapy. Methods: This retrospective study included 100 patients with piriform sinus carcinomas who had received treatment by radiation‐based therapy. The MTV values were obtained from pretreatment positron emission tomography (PET). The association between clinical factors, including the MTV, and survival was analyzed. Results: Kaplan–Meier estimates revealed the 5‐year disease‐free survival (DFS) rates were significantly poorer for patients with a high MTV compared to those with a low MTV. In the multivariate analysis, MTV ( p < .001), nodal metastasis ( p = .011), and applied chemotherapy regimen ( p = .004) were found to be independent prognostic factors for DFS. Conclusion: The locoregional MTV is a prognostic factor for DFS in patients with piriform sinus carcinoma treated by radiation‐based therapy. © 2016 Wiley Periodicals, Inc. Head Neck 38 : 1708–1716, 2016